Studi litelatur tentang kesulitan - Elsyajunita Rita (Jurnal Dharma PGSD, 2026)
This study aims to describe mathematics learning difficulties among elementary school students based on the findings of previous research. Mathematics is one of the fundamental subjects that plays an important role in developing students' logical, critical, systematic, and analytical thinking skills. However, in the learning process, many elementary school students still experience difficulties in understanding mathematical concepts, performing arithmetic operations, solving word problems, and applying mathematical concepts in everyday life. These difficulties are influenced by various factors, including both internal and external factors.This study employed a qualitative approach using a literature review method. The data were collected through the review of scientific journals, research articles, reference books, and other academic documents relevant to the research topic. Documentation was used as the data collection technique, while content analysis was employed as the data analysis technique.The findings indicate that mathematics learning difficulties among elementary school students include difficulties in understanding mathematical concepts, performing calculations, understanding mathematical symbols, and solving problem-solving tasks. The dominant contributing factors include low learning interest, lack of motivation, less varied teaching methods, and limited use of concrete learning media. Therefore, innovative, contextual, and student-centered learning strategies are needed to minimize mathematics learning difficulties.